The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms222313143
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Profiling of Young and Old Brown Adipose Tissue Thermogenesis

Abstract: Brown adipose tissue (BAT) is a major site for uncoupling protein 1 (UCP1)-mediated non-shivering thermogenesis. BAT dissipates energy via heat generation to maintain the optimal body temperature and increases energy expenditure. These energetic processes in BAT use large amounts of glucose and fatty acid. Therefore, the thermogenesis of BAT may be harnessed to treat obesity and related diseases. In mice and humans, BAT levels decrease with aging, and the underlying mechanism is elusive. Here, we compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…To further characterize the early active phase exercise response, the regulation of genes showing previous connections to stress- and adrenergic-responsive processes was investigated. Accordingly, genes responsive to stress or glucocorticoid stimuli (such as Nr4a1, Nr4a3, Vegfα, and Adrb2 ) ( 25 27 ), as well as genes associated with adipose tissue browning and thermogenesis (such as Cpeb2, Cyp2b10, Pdk4, Slc25a25, Cpeb2, Vegfα, Pgc1α, Ucp1, Dio2, Gadd45g, Irf4, Zfp516, and Crem ) ( 28 37 ), were uniquely up-regulated by exercise at the early active phase ( Fig. 2 F ).…”
Section: Resultsmentioning
confidence: 99%
“…To further characterize the early active phase exercise response, the regulation of genes showing previous connections to stress- and adrenergic-responsive processes was investigated. Accordingly, genes responsive to stress or glucocorticoid stimuli (such as Nr4a1, Nr4a3, Vegfα, and Adrb2 ) ( 25 27 ), as well as genes associated with adipose tissue browning and thermogenesis (such as Cpeb2, Cyp2b10, Pdk4, Slc25a25, Cpeb2, Vegfα, Pgc1α, Ucp1, Dio2, Gadd45g, Irf4, Zfp516, and Crem ) ( 28 37 ), were uniquely up-regulated by exercise at the early active phase ( Fig. 2 F ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that the deficiency of Hspa12a, member of the Hsp70 family, promoted greater browning in iWAT of knockout mice compared to wild type during cold exposure and suggested this effect could be mediated through paracrine mechanisms (Cheng et al, 2019). In contrast to the above, Kim et al found that Hsph1, Hsp90aa1, and Hspa8 are upregulated in BAT of young and old mice exposed to acute cold exposure (Kim et al, 2021). In the current study, the expression of Hspa1a and Hspa1b were lower in iWAT compared to BAT and β3adrenergic stimulation through CL further decreased their expression.…”
Section: Discussionmentioning
confidence: 98%
“…RNA sequencing with next-generation sequencing technology has provided a powerful, highly reproducible, and cost-effective tool (Xu et al, 2018). In recent years, transcriptome studies have reported specific molecular mechanisms and candidate genes for cold-exposed humans (Kim et al, 2021), mice (Shore et al, 2013), fish (Xu et al, 2018;Sun et al, 2019;Liu et al, 2020), gray treefrog (Amaral et al, 2020), and shrimp (Zhuo et al, 2020). In the current study, we focused on skeletal muscle, as both ST and NST could contribute to systemic thermoregulation (Fuller-Jackson and Henry, 2018;Roesler and Kazak, 2020;Grigg et al, 2022).…”
Section: Discussionmentioning
confidence: 99%